The Effect of Fartlek Training on Increasing Vo2max Capacity in Futsal Players - Satimin, Satimin; Himawan, Agus; Purwoto, Septyaningrum Putri; Mukti Widodo, Haryo (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
Futsal is a form of indoor soccer played on a smaller field compared to regular soccer, with fewer players on each team. The purpose of this study was to determine the effect of fartlek training on increasing VO2Max of Sinjay FC Bangkalan futsal players. This study used an experimental method with a one group pretest-posttest design. The population in this study were 25 samples and the sampling technique used cluster sampling, which is a sampling method that involves dividing the target population into groups that are made into research samples so that the sample of this study is U 17-18 athletes who follow the Sinjay FC Bangkalan club. Based on the results of the study that there is a significant effect of fartlek training there is an increase in VO2Max futsal club Sinjay FC Bangkalan which has been taken from the pretest with an average of the total initial test of 35.254. With the treatment of fartlek training VO2Max in Sinjay FC Bangkalan futsal athletes can increase. The results of VO2Max measurements after treatment showed that the overall average of the final evaluation showed an increase to 37.992. So that it has been tested by, prerequisite test and hypothesis test from the analysis of research data obtained it can be seen that the Sig value. (2-tailed) of 0.000 <0.05, it can be concluded that there is a difference in the effect of fartlek training on increasing VO2Max athletes who are real between fartlek training and control training. The results of this analysis will show how strong or weak the relationship between fartlek training performed by futsal players and the increase in their VO2Max.